A Social Network Analysis of Football with Complex Networks - Felix, Lucas G. S.; Barbosa, Carlos M.; Vieira , Vinícius da F.; Xavier, Carolina Ribeiro (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
Soccer is the most popular sport in the world and due its popularity, soccer moves billions of euros over the years, in most diverse forms, such as marketing, merchandising, TV quotas and players transfers. As example, in the 2016/2017 season, only England has moved about 1.3 billion of euros only in players transfers. In this work, it is performed a study of the transfer market of player. To do so, players transfer data were gathered from the website Transfermarkt and were modeled as a graph. In order to perform this study, different Complex Networks techniques were applied, such as Overlap Community Detection and Property Analysis. Through our results we could evaluate the soccer players market, and see a pattern that every market has at least one farm country, which has a main function of selling athletes, or a buyer country, which most of its transactions is buying players.